Tinjauan Hukum Islam Terhadap Tip Kurir Cash on Delivery (COD) di Kantor J & T Talang Babat - Annisa Fitri; M Arif Musthofa; Triyana Wulandari; Zeni Sunarti; Al Munip (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study employed a qualitative approach. The data used in this study were primary and secondary data. The field research technique used was file research. 1). Observation, conducted by the author directly by observing various matters related to the writing. 2). Interviews, where the author conducted the writing through an individual approach and directly asked several informants. 3). Documentation, or data collection, conducted by the author by going into the field to collect data or documents that could provide an overview of the location and object. The results of this study showed that many customers gave tips to J&T couriers. From an Islamic perspective, tipping J&T couriers is essentially permissible, especially if the giving is a form of appreciation for good service and not coercion. Tipping J&T couriers is not an obligation, but rather a form of appreciation for the service provided by the courier to the customer, so that the customer feels satisfied with the courier's performance. These tips are given voluntarily without any request or coercion.